2020
DOI: 10.3390/ani10122331
|View full text |Cite
|
Sign up to set email alerts
|

Social Behaviour of Horses in Response to Vocalisations of Predators

Abstract: We tested the hypothesis that social defensive responses to the vocalisation of a predator still exist in horses. The recordings of a grey wolf, an Arabian leopard and a golden jackal were played to 20 Konik polski and Arabian mares. Durations of grazing, standing still, standing alert and the number of steps in walk and trot/canter were measured. In one-minute scans, the distances of the focal horse from the reference horse (DIST-RH) and from the nearest loudspeaker (DIST-LS) were approximated. The vocalisati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(16 citation statements)
references
References 52 publications
(69 reference statements)
1
10
0
Order By: Relevance
“…It was also found that semi-feral and domestic mares form stable herds in the absence of stallions (Sigurjónsdóttir et al 2003;Jaworska et al 2020). Furthermore, the mares in familiar groups were observed to display specific social defence behaviour (spatial group formation) in response to the vocalisation of predators (Janczarek et al 2020).…”
Section: Sex and Social Behaviourmentioning
confidence: 94%
“…It was also found that semi-feral and domestic mares form stable herds in the absence of stallions (Sigurjónsdóttir et al 2003;Jaworska et al 2020). Furthermore, the mares in familiar groups were observed to display specific social defence behaviour (spatial group formation) in response to the vocalisation of predators (Janczarek et al 2020).…”
Section: Sex and Social Behaviourmentioning
confidence: 94%
“…To the presentation of wolf urine [ 27 ] and wolf howl [ 29 ], horses responded with only remote increases in heart rate [ 27 , 29 ] and glucocorticoid rates as well as decreases in heart rate variability [ 29 ], which indicates that they experienced fear but not panic [ 27 , 29 ]. Furthermore, anti-predator responses differed between horse breeds [ 29 , 30 ]. Generally, the strength of horse reactions and attentiveness to predator cues increased with the percentage of thoroughbred ancestry [ 30 ].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, anti-predator responses differed between horse breeds [ 29 , 30 ]. Generally, the strength of horse reactions and attentiveness to predator cues increased with the percentage of thoroughbred ancestry [ 30 ].…”
Section: Introductionmentioning
confidence: 99%
“…Although predators are generally silent while hunting, many species respond to their vocalisation, as it directly indicates the presence of a predator [ 22 , 24 ]. Studies on predator recognition in domestic ungulates show they still exhibit antipredator behaviour when exposed to predators’ odours, sounds or visual signs [ 25 , 26 , 27 ] and thus, these cues may have some potential to modify the grazing activity of prey [ 28 ]. Aflitto and DeGomez [ 29 ] suggest that acoustic stimuli may act as repellents if they are biologically relevant.…”
Section: Introductionmentioning
confidence: 99%